Indonesian Market Concentration on The Non-Oil and Gas Commodity Before and During Covid-19 Pandemic - Lilis Yuliati; Siti Komariyah; Moh. Adenan; Fajar Wahyu Prianto (Signifikan: Jurnal Ilmu Ekonomi, 2022)
The economic growth of a country is inseparable from the balance of trade, mainly the export and import activity. Globalization urges a country to actively socialize and provide infrastructure and facilities to support productivity and improve competitiveness in the international market. Increasing commodity export value affects the balance of trade to reach surplus, and increasing import value causes the balance of trade deficit. This study aims to analyze Indonesia’s non-oil and gas commodity market concentration. Trade Specialization Ratio (TSR) result shows a tendency for Indonesia’s non-oil and gas commodities to be both exporters and importers before and during the COVID-19 pandemic. The strategic plan to increase the product competitiveness in the international market can be in the form of increased productivity and quality; cooperating with several parties such as central and regional government, private parties, and also the general public in the planning for differentiating products and export destination, compliance with international product certification standard, tariff policy, and strengthening the economic institutions within the trade activity. Those efforts are taken to achieve national economic growth and decrease regional economic disparities.How to Cite:Yuliati, L., Komariyah, S., Adenan, M., & Prianto, F. W. (2022). Indonesian Market Concentration on The Non-Oil Gas Commodity Before and During Covid-19 Pandemic. Signifikan: Jurnal Ilmu Ekonomi, 11(2), 289-298. https://doi.org/10.15408/sjie.v11i2.24678.JEL Classification: F10, Q20, C40